EP853 The feasibility of robot-assisted laparoscopic staging in early-stage epithelial ovarian cancer. (1st November 2019) - Karsemeijer, SJ; Zweemer, RP; Verheijen, RHM; Gerestein, CG
Abstract : Introduction/Background: The aim of this study was to evaluate the feasibility and outcomes of robot-assisted laparoscopic staging in early-stage epithelial ovarian cancer. Methodology: Women who received robot-assisted laparoscopic staging procedures for early-stage epithelial ovarian cancer at the University Medical Centre Utrecht, Utrecht, The Netherlands, between March 2012 to December 2017, were retrospectively included in the study. All enrolled cases were reviewed for patient and tumour characteristics, surgical outcomes, postoperative parameters and survival. Results: A total of 27 patients were identified. Median age was 55 years (range 39–74 years). In three (11%) patients, conversion to laparotomy was necessary. Median operating time was 229 min (range 127–312 min) and median blood loss was 50 mL (range 30–200 mL). Median pelvic lymph node yield was 14 (range 5–24), median para-aortic lymph node yield was 5 (range 1–17), and median total lymph node yield was 20 (range 10–39). No perioperative complications were observed. One (4%) patient had a postoperative complication without long-term consequences. There was one (4%) case found to be upstaged. Median postoperative pain score was NRS 4 (range NRS 0–7) and median 24–48 h postoperative pain score was NRS 3 (range NRS 0–6). Median time until full diet resumption was 1.5 day (range 1–3 days), median time until self-mobilizing was 1.5 day (range 1–2 days), and median duration of hospital stay was 2.5 days (range 1–5 days). The median duration of follow up was 13 months (range 0–69 months). The median disease free interval was 40 months (range 12–47 months), the disease free survival was 88%, and the overall survival was 96%. Conclusion: Robot-assisted laparoscopic staging is feasible and safe for the management of early-stage epithelial ovarian cancer. Further prospective studies, and longer follow-up periods will be necessary to confirm our results in terms of complications, comprehensiveness, and disease recurrence. Disclosure: Nothing to disclose.